Beamforming with opportunistic relaying for wireless security. Issue 8 (1st May 2014) - Sarkar, Mohammad Zahurul Islam; Ratnarajah, Tharmalingam; Ding, Zhiguo
Abstract : The authors present a beamforming scheme with opportunistic relaying (namely opportunistic beamforming) for wireless security under amplify‐and‐forward (AF) and decode‐and‐forward (DF) strategies. The relay selection is performed using the method of distributed timers, where all the relays use their timers to estimate own instantaneous channel gains and compete to access the wireless medium according to their own channel conditions. The performance of opportunistic beamforming scheme in terms of secure outage probability is analysed and the beamforming problem as a semidefinite programming problem with its optimisation framework is formulated. The results show that, in an opportunistic beamforming scheme, competition among cooperative relays offers diversity benefits in the direction of destination that enhances secrecy rate (i.e. minimises secure outage probability) and adhere to the 'opportunistic' cooperation rule giving priority to the 'best' available relay even when they are not chosen to transmit but rather chosen to cooperatively listen. Opportunistic beamforming scheme with DF strategy enhances secrecy rate than the beamforming with multiple DF relays while in the case of AF strategy, it provides significant improvement in the secrecy rate compared to the opportunistic relaying, the equal‐power multiple‐relay transmission and the single‐relay transmission schemes.